Spatial Control of Neuronal Adhesion on Diamond-Like Carbon - Dugan, James M; Colominas, Carles; Garcia-Granada, Andrés-Amador; Claeyssens, Frederik (Frontiers in Materials, 2021)
This study reports a route to spatial control of neuronal adhesion onto Diamond-Like-Carbon (DLC) by surface functionalisation by poly(oligo-ethyleneglycol methacrylate) (pOEGMA) and consequent laser ablation to produce cell adhesive tracks. DLC can be deposited as a tough and low friction coating on implantable devices and surgical instruments and has favourable properties for use as a biomaterial. The pOEGMA surface coating renders the DLC surface antifouling and the laser ablation creates graphitised tracks on the surface. The surfaces were coated with laminin, which adhered preferentially to the ablation tracks. The patterned surfaces were investigated for neuronal cell growth with NG108-15 cells for short term culture and rat neural stem cells for longer term culture. The cells initially adhered highly selectively to the ablation tracks while longer term cell culture revealed a more uniform cell coverage of the surface.